(3YbO TQGA ahGJjQ GdOjhf GdJLGQjI (BFactoring (3ef GdhLgJjf GdYedjI hGdbGfhfjI (B/s - (3NdjaiI, PcQj YHO GdQGRb eMeO s ((3GdEScfOQjI, eUQ (B:s (3OGQ GdLGeYI GdLOjOI,s, 2017)
(3cGf GgJeGe Gdabg HYbO TQGA GdMbhb GdJLGQjI GdKGHJI aj ahGJjQ, eMGhdG JMOjO GdEWGQ GdbGfhfi hGdJfXjei dgPG GdYbO Ydj VhA GdhXjaI GdEbJUGOjI Hjf CWQGag(B. (3hYdi eG JbOe aEffG Sha fbhe aj gPg GdOQGSI HGdJYQV dHjGf eaghe YbO TQGA ahGJjQ GdOjhf GdJLGQjI hHjGf UhQg GdYedjI, hLOhGg GdEbJUGOjI ddeTQhYGJ GdJLGQjI, hPdc hUhdG Edi eMGhdI JMOjO WHjYJg GdbGfhfjI, hef Ke GdBKGQ GdJj jQJHgG Hjf WQajg(B. (3hYdjg aEffG SfJfGhd gPG GdYbO aj aUdjf Ydj GdfMh GdJGdj (B: (3GdaUd GdChd (B: (3YbO TQGA GdahGJjQ aj GdEWGQ GdYedj, GdaUd GdKGfj (B: (3GdWHjYI GdbGfhfjI dYbO TQGA ahGJjQ GdOjhf GdJLGQjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B127-131.s
Keywords: (3GdOjhfs -- (3bhGfjf hJTQjYGJs; (3GdYbhO (B((3bGfhf eOfj(B)s; (3GdJNUje (B((3eGdjI(B)s -- (3bhGfjf hJTQjYGJs